SOCIAL MEDIA TECHNOLOGY IN IMPROVING MARKETING OF SHARIA INSURANCE PRODUCTS (TAKAFUL) TO ISLAMIC BANKING ACADEMICS - Rohimah, Wasilatur; Rofika, Haniatur; Meylianingrum, Kurniawati; Mounadi, Abdelaziz; Asnawi, Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
Indonesia, one of the countries with the largest Muslim majority in the world, can develop opportunities for sharia-based insurance ( takaful ). Nowadays technological developments have changed the marketing strategy of sharia insurance. Thus, the purpose of study is to find out how far influence technology and social media have in increasing sharia insurance marketing. Meanwhile, the research method used was descriptive qualitative, and the object was sharia insurance institution customers with digitalization of technology and social media. This research was implemented on sharia banking course materials. Based on the research results, people's activities today prioritize the use of technology and digitization. Especially during the pandemic, people make transactions through digital media. This affects the activities of sharia insurance which used to do direct marketing, now it was done through online. Hence, the target consumer becomes more because the reach knows no boundaries. In addition, as many as 70% of respondents knew about sharia insurance through social media. In other words, marketing sharia insurance using social media has higher reach and opportunities than other manual promotion systems.